The Surgical Management of Haemorrhoids - A Historical Perspective - Keval Patel; Samuel Stefan; Syed Naqvi; Jim S. Khan (Aziz Fatimah Medical and Dental College, 2019)
SUMMARY Haemorrhoids have affected people since ancient time. First documented treatment for haemorrhoids reported from the Egyptian papyrus. Indeed, Ebers' papyrus dated at 1550 BC, described the use of topical astringents to ease haemorrhoidal pain. More recently, the Milligan-Morgan haemorrhoidectomy and office procedures such as rubber-band ligation have been developed to improve patients' symptoms. However, these treatments have accompanying problems, for example the haemorrhoidectomy is known to be a profoundly painful operation and office procedures have high recurrence rates and are only suitable for minor haemorrhoids. The development of stapled haemorrhoidopexy and Transanal Haemorrhoidal Dearterialisation (THD) procedures, present the opportunity to treat all grades of haemorrhoids, with improved post-operative pain, whilst maintaining a low recurrence rate. This article places these more modern techniques in the context of the long history of surgical treatments for haemorrhoids and reviews the latest literature comparing operative haemorrhoidectomy, stapled haemorrhoidopexy and THD. A systematic review was carried out to retrieve articles describing history of surgical management of haemorrhoids and studies comparing three modern treatments for haemorrhoids (Haemorrhoidectomy, Stapled haemorrhoidectomy, and THD) were reported.